2016
DOI: 10.1007/s00701-016-3055-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic resonance imaging in the evaluation of peripheral nerves following traumatic lesion: where do we stand?

Abstract: These seven articles were subsequently evaluated by analyzing their results, methodological approach, and conclusions presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…MRI is the gold standard for examining the BP. Nevertheless, the large field of view of MRI makes it impossible to analyze the fine nerve structures of the BP individually (Ohana et al, ; Marquez Neto et al, ). Fornage et al () showed that US was superior for studying the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is the gold standard for examining the BP. Nevertheless, the large field of view of MRI makes it impossible to analyze the fine nerve structures of the BP individually (Ohana et al, ; Marquez Neto et al, ). Fornage et al () showed that US was superior for studying the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the gold standard for describing the BP and its terminal branches (Boykin et al, ; Chalian et al, ; Ahlawat et al, ; Marquez Neto et al, ; Wang et al, ). During the last two decades, ultrasonography (US) of the suprascapular portion of the SSN has gained prominence for the dynamic exploration of neuropathies and for ultrasound‐guiding of anesthetic nerve blocks in cases of acute and chronic shoulder pain (Karataş et al, ; Boykin et al, ; Chan et al, ; Stein et al, ; Bharti et al, ; Lewis et al, ; Chang et al, ; Dhir et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, neural tissue regeneration takes a relatively long time that may take several weeks 27 , 28 . Therefore, scaffolds for neural tissue regeneration should have long-term biodegradable time to provide a long enough time for nerve regeneration and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The anatomy of this region has now been described in great detail with regard the course of the PIN (Ebraheim et al., 2000) as well its specific relationship with the supinator muscle (Thomas et al., 2000). MRI can be used to visualize any extrinsically compressive lesion and the recent advent of 3.0 Tesla MRI neurography should increase the usefulness of this imaging modality even further (Marquez Neto et al., 2017; Wang et al., 2017). Ultrasound can be useful for quantifying the degree of constriction seen in compressive neuropathy and HLFC (Ong et al., 2014; Nakamichi et al., 2007), but its other advantage is in combination with needle EMG, improving the accuracy of needle placement (Wininger et al., 2015).…”
Section: Resultsmentioning
confidence: 99%